(untitled) (Proceeding of SINERGY, 2026)
Palmarosa (Cymbopogon martinii) is an important aromatic plant widely utilized as a source of essential oil with significant economic value. Genetic improvement of palmarosa is required to enhance plant performance and productivity, and one effective approach is induced mutation using gamma-ray irradiation. Gamma irradiation is known to generate random genetic variation that may affect plant growth and development. This study aimed to evaluate the effects of different gamma-ray irradiation doses on vegetative growth characteristics of palmarosa and to identify responsive traits for further breeding programs. The experiment was conducted using a Randomized Complete Block Design (RCBD) with a single factor consisting of eight levels of gamma-ray irradiation doses. Gamma irradiation treatment was performed at the National Research and Innovation Agency (BRIN), planting was carried out in Plasansari Village, Semarang, Indonesia, and data analysis was conducted at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang (UNNES). Vegetative parameters observed at the final growth stage included plant height, stem diameter, number of leaves, and number of tillers. The collected data were subjected to analysis of variance (ANOVA), and significant differences among treatments were further analyzed using Duncan’s Multiple Range Test at a 5% significance level. The results showed that gamma-ray irradiation had no significant effect on plant height of palmarosa. However, block effects significantly influenced plant height, indicating that environmental variation among blocks contributed to differences in plant growth. In contrast, gamma-ray irradiation treatments significantly affected the number of leaves and tiller numbers. These results indicate that gamma irradiation can induce variability in specific vegetative traits, particularly those related to canopy development and tillering capacity. The results indicate that gamma-ray irradiation is a promising mutagen for inducing useful phenotypic variation in palmarosa. This study provides baseline information for palmarosa mutation breeding and emphasizes the importance of selecting appropriate vegetative traits in early- generation evaluation to support the development of improved genotypes for essential oil production.